BENDUNGAN ASI, SEBUAH LAPORAN KASUS ASUHAN NIFAS (Jurnal Kesehatan Siliwangi, 2022)
Breast engorgement happens when venous and lymphatic flow are clogged, milk flow becomes blocked and there are pressure enhancement on both breast milk ducts and alveoli. If the breast engorgement is not properly handled, it will cause mastitis and even breast abscess. The purpose of this care was to carry out postpartum midwifery care appropriately so that complications didn’t occur. The methodology used was case study with midwifery management approach based on in the form of subjective, objective, analytical, and management documentation (SOAP) with the results obtained after monitoring that the patient complains fever, pain and swelling on the left breast and inverted nipple, so that analysis that enforced Mrs A, 24 years old, 2 days postpartum with breast engorgement. The care provided was breast care, breastfeeding techniques and how to deal with inverted nipple. The conclusion was care provided according to the patient’s needs according to standard operating procedures (SOP) at the first health service place. No gaps were found between theory and practice, the breast engorgement was overcome and the baby was able to suckle well. Suggestions for clients and families were to apply breastfeeding techniques continuously so as to avoid lactation problems, escpecially breast engorgement.